The highs and lows of programmed cardiovascular disease by developmental hypoxia: studies in the chicken embryo - Itani, N. (J Physiol, 2017)
It is now established that adverse conditions during pregnancy can trigger a fetal origin of cardiovascular dysfunction and/or increase the risk of heart disease in later life. Suboptimal environmental conditions during early life that may promote the development of cardiovascular dysfunction in the offspring include alterations in fetal oxygenation and nutrition as well as fetal exposure to stress hormones, such as glucocorticoids. There has been growing interest in identifying the partial contributions of each of these stressors to programming of cardiovascular dysfunction. However, in humans and in many animal models this is difficult, as the challenges cannot be disentangled. By using the chicken embryo as an animal model, science has been able to circumvent a number of problems. In contrast to mammals, in the chicken embryo the effects on the developing cardiovascular system of changes in oxygenation, nutrition or stress hormones can be isolated and determined directly, independent of changes in the maternal or placental physiology. In this review, we summarise studies that have exploited the chicken embryo model to determine the effects on prenatal growth, cardiovascular development and pituitary–adrenal function of isolated chronic developmental hypoxia. [Image: see text]